EXPLORING NEW FEATURES FOR THE PERTURBED CHEN-LEE-LIU MODEL VIA (Formula Presented) EXPANSION METHOD - Bulut, Hasan; Ismael, Hajar F. (Institute of Mathematics and Mechanics, National Academy of Sciences of Azerbaijan, 2022)
In this work, the perturbed Chen-Lee-Liu equation, which describes the propagation of an optical pulse in plasma and optical fiber is studied. The (m +1G? )-expansion method is used for this purpose. As a result, bright-singular, dark-singular, dark and periodic optical soliton waves are constructed. Specific values for the parameters under conditions are also provided to display the pulse propagation of the found solutions. © 2022, Institute of Mathematics and Mechanics, National Academy of Sciences of Azerbaijan. All rights reserved.
Keywords: analytical method; Chen-Lee-Liu equation; Exact solutions